2008
DOI: 10.4238/vol7-4gmr522
|View full text |Cite
|
Sign up to set email alerts
|

MOMO syndrome associated with autism: a case report

Abstract: AbSTRACT. This is a case report of macrosomia, obesity, macrocephaly and ocular abnormalities (MOMO syndrome) associated with autism. Studies on genetic or environmental syndromes associated with autism can provide genetic markers or uncover relevant events, and are very important for the definition of autism subgroups in future molecular research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Nevertheless, no relevant studies or case reports were identified during the last decade, probably diminishing the possibility of this association), Jacobsen syndrome [Fisch et al, 2010], Joubert syndrome (Although there are a few case reports of Joubert patients with ASD [Holroyd et al, 1991; Ozonoff et al, 1999; Kumandas et al, 2004], there is more recent opposite evidence, supporting that the two disorders are distinct [Braddock et al, 2006] and their clinical similarities may be due to cerebellar abnormalities present in both conditions. Nevertheless, common variation in AHI1 , which causes Joubert syndrome type 3, was reported to contribute to ASD risk [Alvarez Retuerto et al, 2008]), Juvenile dentatorubral‐pallidoluysian atrophy [Licht and Lynch, 2002], Kabuki syndrome or Niikawa–Kuroki syndrome [Ho and Eaves, 1997; Akin Sari et al, 2008], KBG syndrome [Hah et al, 2009], Kleefstra Syndrome (http://www.ncbi.nlm.nih.gov/pubmed?term=kleefstra%20pagon), Kleine Levin syndrome [Berthier et al, 1992; Mukaddes et al, 2009], Leber's congenital amaurosis (The initial association with ASD [Rogers and Newhart‐Larson, 1989] has been diminished by recent studies reporting mild only autistic traits in a small minority of children with Leber's [Fazzi et al, 2007; den Hollander et al, 2008]), Leopard syndrome [Watanabe et al, 2010], Leukocyte adhesion deficiency type II [Gazit et al, 2010], Marineso Sjogren syndrome [Sponheim and Skjeldal, 1998], Miller–Dieker syndrome (two personal cases), MOMO syndrome [Giunco et al, 2008], Myhre syndrome [Titomanlio et al, 2001], Neuroaxonal dystrophy [Weidenheim et al, 2001], New neurocutaneous syndrome [Buoni et al, 2006; Zannolli et al, 2008], Nicolaides–Baraitser syndrome [Gana et al, 2011], Noonan syndrome [Ghazziudin et al, 1994], Ocolocutaneous albinism [Delong, 2007; Bakare and Ikegwuonu, 2008], Orstavik syndrome [Orstavik et al, 1997], PARK2 microdeletion/microduplication syndrome [Scheuerle and Wilson, 2011], Potocki–Shaffer syndrome [Swarr et al, 2010]. Rett syndrome variants (e.g., FOXG1 syndrome or Zapella variant) [Renieri et al, 2009; Kortüm et al, 2011], Rubinstein taybi syndrome [Levitas and Reid, 1998; Hellings et al, 2002; Schorry et al, 2008; Galéra et al, 2009], Septo optic dysplasia [Polizzi et al, 2006; Parr et al, 2010], Sturge–Weber syndrome (three personal cases) Trichothiodystrophy syndrome [Schepis et al, 1997], Unilateral cerebellar hypoplasia [Ramaekers et al, 1997], Unilateral ...…”
Section: Other Syndromesmentioning
confidence: 99%
“…Nevertheless, no relevant studies or case reports were identified during the last decade, probably diminishing the possibility of this association), Jacobsen syndrome [Fisch et al, 2010], Joubert syndrome (Although there are a few case reports of Joubert patients with ASD [Holroyd et al, 1991; Ozonoff et al, 1999; Kumandas et al, 2004], there is more recent opposite evidence, supporting that the two disorders are distinct [Braddock et al, 2006] and their clinical similarities may be due to cerebellar abnormalities present in both conditions. Nevertheless, common variation in AHI1 , which causes Joubert syndrome type 3, was reported to contribute to ASD risk [Alvarez Retuerto et al, 2008]), Juvenile dentatorubral‐pallidoluysian atrophy [Licht and Lynch, 2002], Kabuki syndrome or Niikawa–Kuroki syndrome [Ho and Eaves, 1997; Akin Sari et al, 2008], KBG syndrome [Hah et al, 2009], Kleefstra Syndrome (http://www.ncbi.nlm.nih.gov/pubmed?term=kleefstra%20pagon), Kleine Levin syndrome [Berthier et al, 1992; Mukaddes et al, 2009], Leber's congenital amaurosis (The initial association with ASD [Rogers and Newhart‐Larson, 1989] has been diminished by recent studies reporting mild only autistic traits in a small minority of children with Leber's [Fazzi et al, 2007; den Hollander et al, 2008]), Leopard syndrome [Watanabe et al, 2010], Leukocyte adhesion deficiency type II [Gazit et al, 2010], Marineso Sjogren syndrome [Sponheim and Skjeldal, 1998], Miller–Dieker syndrome (two personal cases), MOMO syndrome [Giunco et al, 2008], Myhre syndrome [Titomanlio et al, 2001], Neuroaxonal dystrophy [Weidenheim et al, 2001], New neurocutaneous syndrome [Buoni et al, 2006; Zannolli et al, 2008], Nicolaides–Baraitser syndrome [Gana et al, 2011], Noonan syndrome [Ghazziudin et al, 1994], Ocolocutaneous albinism [Delong, 2007; Bakare and Ikegwuonu, 2008], Orstavik syndrome [Orstavik et al, 1997], PARK2 microdeletion/microduplication syndrome [Scheuerle and Wilson, 2011], Potocki–Shaffer syndrome [Swarr et al, 2010]. Rett syndrome variants (e.g., FOXG1 syndrome or Zapella variant) [Renieri et al, 2009; Kortüm et al, 2011], Rubinstein taybi syndrome [Levitas and Reid, 1998; Hellings et al, 2002; Schorry et al, 2008; Galéra et al, 2009], Septo optic dysplasia [Polizzi et al, 2006; Parr et al, 2010], Sturge–Weber syndrome (three personal cases) Trichothiodystrophy syndrome [Schepis et al, 1997], Unilateral cerebellar hypoplasia [Ramaekers et al, 1997], Unilateral ...…”
Section: Other Syndromesmentioning
confidence: 99%
“…However, there is certain variability between the reported cases. The oldest patient was reported at the age 29 years, he showed ID and fulfilled the diagnostic criteria for autism [Giunco et al, 2008]. The other patient, described at the age 13 years, had mental deficiency associated with “schizoid” behavior and irritability (Patient 1 in Moretti‐Ferreira et al [1993]).…”
Section: Discussionmentioning
confidence: 99%
“…However, a third patient published in 2000 had short stature and overgrowth was discussed as non‐mandatory for the diagnosis [Zannolli et al, 2000]. The next report appeared in Giunco et al [2008] describing a patient with tall stature and proposed diagnosis of MOMO syndrome in association with autism. The fifth patient considered to have MOMO syndrome had a height within the normal range (50th centile), although Kabuki syndrome was discussed as a differential diagnosis [Wallerstein and Sugalski, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Later on more single case reports were added by Zannolli et al in 2000 [4], Giunco et al in 2008 [5], and the most recent addition by Wallerstein and Sugalski in 2010 [1]; thus expanding the spectrum of clinical manifestation in this syndrome. …”
Section: Discussionmentioning
confidence: 99%
“…Obesity syndromes have variable clinical manifestation often involving multiple systems. Some may even have overlapping symptoms [5] which indicates a common pathway in the mechanism of obesity and thus can help us identify the molecular mechanisms involved in their etiology. Molecular basis of Bardet-Biedl syndrome has been recently identified, confirming it to be an oligogenic disorder.…”
Section: Discussionmentioning
confidence: 99%